Vaccination coverage among children under one year of age in the Agreste region of Pernambuco from 2019 to 2023: A descriptive analysis (Research, Society and Development, 2026)
Objective: To analyze vaccination coverage among children under one year of age in the 21 municipalities of the V Regional Health Management of Pernambuco from 2019 to 2023, comparing coverage rates across localities. Methods: This is a descriptive and retrospective epidemiological study using secondary data from the Department of Informatics of the Brazilian Unified Health System. Mean vaccination coverage rates (frequency measure) were calculated for the following vaccines: BCG, Hepatitis B, Pentavalent, Poliomyelitis, Pneumococcal, Rotavirus, Meningococcal C, and Yellow Fever. Analysis of variance and Tukey’s test were applied to assess dispersion and statistical differences among municipalities. Results: Analysis of aggregated data indicated that mean regional vaccination coverage remained below the 95% target recommended by the Ministry of Health. Specifically, the Pentavalent vaccine showed a mean coverage of 88.08%, and the Meningococcal C vaccine reached 85.27%. Statistical tests revealed heterogeneity in coverage rates among the evaluated municipalities. Conclusion: The V Regional Health Management of Pernambuco presented insufficient immunization rates during the study period, failing to achieve collective protection targets. The statistical disparities identified among municipalities highlight areas of greater vulnerability that compromise the effectiveness of the regional immunological barrier.